KINERJA PENYEDIA JASA DALAM PENGENDALIAN MUTU PEKERJAAN CEMENT TREATED RECYCLING BASE PADA PAKET PENINGKATAN JALAN LINGKAR LUAR MUARA TEWEH - Bambang Raharmadi (Universitas Lambung Mangkurat, 2016)
Quality control is one factor supporting the success of the implementation of the results of the work in the field, especially the implementation of road construction. To get the quality of materials and execution of technical specifications which meet the requirements of many things that must be considered, especially human resource capabilities truly professional in managing the quality management and adequate laboratory equipment. Ability, skill and adequate equipment in the testing and reporting right is the key to success in quality control. This study aims to determine the performance of service providers in quality control work Recycling Cement Treated Base (CTRB) in the implementation in the field. The procedures performed in the implementation of quality control is to make the mixture work plan (JMF) and testing during implementation of the work. Quality control consisted of testing material old road / existing with cement content of 7% of the dry weight to determine the physical properties and mechanical by examiners grading grain, the limits of Atterberg, compaction modified and robust press is free (UCS) in laboratory and experimental field compaction and density testing field with Sand Cone of sta 0 + 000 s / d 1 + 900.The test results of material CTRB to test grain size distribution of recycled materials JMF and during the implementation of all eligible permitted, including the CL-ML ie silt is not organic, clay kepasiran with plasticity low based on land classification system USCS while according to the soil classification system AASHTO included in group A-4 ie silt loam soil with low plasticity. JMF in the laboratory obtained gdmax 2.135 t / m3 optimum moisture content of 7.80% and for the implementation of gdmax obtained 2.130 t / m3 optimum moisture content of 7.90%. JMF UCS7hr 30.371 kg / cm2 and during the execution of all the test results showed ≥ 30 kg / cm2 eligible. Compaction experiments for the results of Test pit and density CTRB in the field using sand cone method with the results of the solid thick 30.30 cm ≥ 30 cm of thick design with a degree of field density 100.35%> 95% meet the requirements. CTRB density in the field using sand cone test compaction method for the implementation of all the results obtained degrees density of> 95% qualified